Predictors of Response to Intradetrusor Botulinum Toxin-A Injections in Patients with Idiopathic Overactive Bladder - Brian L. Cohen; Daniel J. Caruso; Prashanth Kanagarajah; Angelo E. Gousse (Advances in Urology)
Objectives. To evaluate whether there are any demographic or urodynamic differences in patients with idiopathic overactive bladder (I-OAB) that respond and do not respond to intradetrusor injections of botulinum toxin-A (BTX-A). Methods. This represents a secondary analysis of data collected from an investigator initiated randomized trial designed to evaluate clinical differences in outcomes for 100 versus 150 U BTX-A in patients with I-OAB. Preinjection demographic and urodynamic data were collected. Patients were evaluated 12 weeks after injection and were determined to be responders or nonresponders as defined by our criteria. Statistical comparisons were made between groups. Results. In patients with overactive bladder without incontinence (OAB-Dry), there were no variables that could be used to predict response to BTX-A. On univariate analysis, younger patients with overactive bladder with incontinence (OAB-Wet) were more likely to respond to BTX-A than older patients. However, this relationship was no longer statistically significant on multivariate analysis. Conclusions. We were unable to identify any preinjection demographic or urodynamic parameters that could aid in predicting which patients will achieve clinical response to BTX-A. Future studies are necessary to further evaluate this question.